A novel (La0.2Ce0.2Gd0.2Er0.2Tm0.2)2(WO4)3 high-entropy ceramic material for thermal neutron and gamma-ray shielding. (July 2021) - Zhang, Xuesong; Li, Yuguang; Li, Changxiang; Yang, Fan; Jiang, Zhengming; Xue, Liyan; Shao, Zhiheng; Zhao, Zhigang; Xie, Meiying; Yu, Shuwen
Graphical abstract: Highlights: (La0.2 Ce0.2 Gd0.2 Er0.2 Tm0.2 )2 (WO4 )3 ceramic was prepared by solid-phase synthesis. (La0.2 Ce0.2 Gd0.2 Er0.2 Tm0.2 )2 (WO4 )3 /epoxy resin blocks more than 99% of neutrons. The lead equivalent of EP/W3 exceeds 0.43 mmPb at 65 keV. The composite materials have completed standard testing. Abstract: In this study, a new type of (La0.2 Ce0.2 Gd0.2 Er0.2 Tm0.2 )2 (WO4 )3 single-phase high-entropy ceramic (HEC) powder was designed, prepared by solid-phase synthesis, and evenly mixed into an epoxy resin (EP) matrix to test the thermal neutron and γ-ray shielding performance. In terms of γ-ray shielding, (La0.2 Ce0.2 Gd0.2 Er0.2 Tm0.2 )2 (WO4 )3 showed a higher lead equivalent value than EP at 65 keV, indicating a clear shielding effect in the feeble absorbing area of lead-based and bismuth-based materials; moreover, (La0.2 Ce0.2 Gd0.2 Er0.2 Tm0.2 )2 (WO4 )3 showed good γ-ray shielding performance in both low-energy and medium-energy regions. In terms of thermal neutron shielding, the composite with the highest HEC content (EP/W3) had a nearly 100% shielding efficiency, while that of EP was approximately 50%, indicating that this material has favorable thermal neutron and γ-ray shielding performance. Moreover, the thermal conductivity of the resulting composite material was lower than 0.3 W·m −1 ·K −1, the tensile strength was higher than 10 MPa, and the density was lower than 1.5 g·cm −3 . All these results suggest that (La0.2 Ce0.2 Gd0.2 Er0.2 Tm0.2 )2 (WO4 )3 is a candidate radiation shielding material.